2012
DOI: 10.5146/tjpath.2012.01106
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of the lung associated with neurofibromatosis type 1: a case report

Abstract: Neurofibromatosis or von Recklinghausen's disease is the most common inherited syndrome predisposing to neoplasia. Carcinosarcoma is a rare malignant mixed tumor of the lung. Association of carcinosarcoma of lung with Neurofibromatosis-1 is not common. A 57-year-old man presented with history of fever, cough, hemoptysis, breathlessness, weight loss, chest pain. Multiple cutaneous neurofibromas and café au lait spots were revealed by physical examination. A homogeneous opacity was found in the right middle and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The most frequent epitheliel component is squamous carcinoma and sarcomatous compenent is rhabdomyosarcoma. Our two patients also had the two components just like the literature [8,10]. In the literature, fewer than 20 cases are reported until 1995 [11][12][13][14].…”
Section: Discussionsupporting
confidence: 70%
“…The most frequent epitheliel component is squamous carcinoma and sarcomatous compenent is rhabdomyosarcoma. Our two patients also had the two components just like the literature [8,10]. In the literature, fewer than 20 cases are reported until 1995 [11][12][13][14].…”
Section: Discussionsupporting
confidence: 70%
“…A review from Japan 20 years ago reported only 11 cases of NF-1 with lung cancer [6], and we interestingly were able to find 7 more cases up to now—without including the presented case—also from the Japanese literature [713]. Adenocarcinoma was the most frequent histological diagnosis (72.9%) in the first 11 cases reviewed, while the following 6 cases were diagnosed as nonsmall cell cancer (3 cases) [9, 11, 12], small cell cancer (1 case) [10], poorly differentiated cancer (1 case) [7], adenocarcinoma (1 case) [8], and carcinosarcoma (1 case) [13]. Smoking habit was not always mentioned in the reported cases in the literature, but there were some patients that were never smokers as in our case [8, 13].…”
Section: Discussionmentioning
confidence: 88%
“…Adenocarcinoma was the most frequent histological diagnosis (72.9%) in the first 11 cases reviewed, while the following 6 cases were diagnosed as nonsmall cell cancer (3 cases) [9, 11, 12], small cell cancer (1 case) [10], poorly differentiated cancer (1 case) [7], adenocarcinoma (1 case) [8], and carcinosarcoma (1 case) [13]. Smoking habit was not always mentioned in the reported cases in the literature, but there were some patients that were never smokers as in our case [8, 13]. In our patient, histology revealed a well-differentiated adenocarcinoma, which is also the most common histological type of lung cancer in nonsmokers, who are by far more common in women [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Neurofibromatosis with primary lung spindle cell carcinoma is a very rare presentation. 10 Bhargava et al reported one case of malignant transformation of cutaneous neurofibroma to cutaneous spindle cell carcinoma. 11 conclusion Pulmonary spindle cell tumor is a rare condition with a non-specific clinical presentation like non-small cell carcinoma of the lung associated with cutaneous neurofibroma; hence pathological and immunohistochemical staining is needed to differentiate.…”
Section: Discussionmentioning
confidence: 99%